Freshwater fish: the overlooked alternative - Bakar, Jamilah (Universiti Putra Malaysia Press, 2009)
The marine fish supply has been dwindling for the past decades, although it was once thought to be inexhaustible. World capture of fish for food rose dramatically from 1973 to 1997 resulting in over exploitation, which was followed by a subsequent decline in world catch, the contrary world per capita food fish consumption has risen due to the increase in world population. Globally, attempts are being made to address the issues on sustaining the supply of marine fisheries; however, this is still not sufficient to ensure world food security. The domestic fish production in Malaysia for year 2007 was estimated at 1.5 million mt, mainly from marine capture fisheries which accounted for 1.2 million mt and the rest from the aquaculture sector. Malaysia is still a net importer of fish and fishery products. The present scenario of rising food prices and the need to feed the increasing world population, has caused the world to turn to aquaculture, which is said to be the fastest growing food sector in the world food production industry. With the fast growing urban population, the food manufacturing industry has to grow and flourish at the same rate or perhaps faster. The insufficient supply of marine fish, the traditional raw material, is slowly inching into the industry. Hence, to sustain this food manufacturing sector, an alternative raw material supply has to be looked into. This lecture, therefore, tries to examine, from the scientific and technological point of view, the possibilities of freshwater fish being utilized as food, raw material and as an ingredient to support the activities of the food manufacturing industry at large.